The role of long non-coding RNA ANRIL in the development of atherosclerosis - Ilgiz Gareev; Valentin Kudriashov; Albert Sufianov; Sema Begliarzade; Tatiana Ilyasova; Yanchao Liang; Ozal Beylerli (Non-coding RNA Research, 2022)
Atherosclerosis is an important pathological basis of coronary heart disease, and the antisense non-coding RNA in the INK4 locus (ANRIL) is located in the genetically susceptible segment with the strongest correlation with it - the short arm 2 region 1 of chromosome 9 (Chr9p21). ANRIL can produce linear, circular and other transcripts through different transcriptional splicing methods, which can regulate the proliferation and apoptosis of related cells and closely related to the development of atherosclerotic plaques. Linear ANRIL can regulate proliferation of vascular smooth muscle cells (VSMCs) in plaques by chromatin modification, as well as affecting on proliferation and the apoptosis of macrophages at the transcriptional level; circular ANRIL can affect on proliferation and apoptosis of VSMCs by chromatin modification as well as interfering with rRNA maturation. In this review we describe the evolutionary characteristics of ANRIL, the formation and structure of transcripts, and the mechanism by which each transcript regulates the proliferation and apoptosis of vascular cells and then participates in atherosclerosis.